Penyuluhan Tentang Sindroma Metabolik Sebagai Resiko Untuk Terjadinya Penyakit Degeneratif Dan Cara Pencegahannya - Antin Trilaksmi; Diani Nazma; Lira Panduwaty; Christian; Karlina Mahardieni; Noviani Prasetyaningsih (CV. Multi Kreasi Media, 2024)
Metabolic syndrome has become a global epidemic with a widespread increase in obesity cases. The prevalence of metabolic syndrome is quite high and varies between populations of different ethnicities. Hypertension is a major contributor to the prevalence of metabolic syndrome and abdominal fat is strongly associated with metabolic syndrome. Metabolic syndrome increases the risk of various degenerative diseases, for example type 2 DM, cardiovascular disease, stroke, heart infarction and the risk of death from the above degenerative diseases. Lifestyle modification combined with diet and exercise remains the initial intervention to reduce the risk of metabolic syndrome.This Community Service Activity is aimed at providing additional knowledge about healthy lifestyle patterns that can prevent or control metabolic syndrome, so that it is hoped that people can apply it in their daily lives and ultimately reduce the rate of morbidity and mortality due to metabolic syndrome. The activity was carried out at the Trisakti Nagrak campus, Ciangsana village, Gunung Putri sub-district, Bogor, December 3 2023. Counseling is carried out using the lecture method and ends with questions and answers. Participants are given pre-test and post-test questions before and after the counseling session to assess how far the participants' related knowledge has increased.